2021
DOI: 10.3390/medicina57060602
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cortisol Index of Endobiogeny in Acute Myocardial Infarction Patients

Abstract: Background and Objectives: Serum cortisol has been extensively studied for its role during acute myocardial infarction (AMI). Reports have been inconsistent, with high and low serum cortisol associated with various clinical outcomes. Several publications claim to have developed methods to evaluate cortisol activity by using elements of complete blood count with its differential. This study aims to compare the prognostic value of the cortisol index of Endobiogeny with serum cortisol in AMI patients, and to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The latter two are rapid, cost effective, and easily repeated throughout hospitalization. We (KMH, JCL) have demonstrated the value of this approach to modeling in predicting mortality on admission for patients admitted with acute myocardial infarction ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter two are rapid, cost effective, and easily repeated throughout hospitalization. We (KMH, JCL) have demonstrated the value of this approach to modeling in predicting mortality on admission for patients admitted with acute myocardial infarction ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue levels have not consistently been associated with severity of illness ( 13 , 14 ). Our group (KMH, JCL) has demonstrated that the effective tissue-level activity of cortisol can be modeled using a complete blood count with differential (CBC) ( 15 ) in chronic heart failure and acute myocardial infarction (AMI) ( 16 , 17 ) and that the model of admission cortisol activity was superior to serum cortisol in predicting mortality in AMI ( 17 ). The formation of the index is based on the observation that cortisol increases erythrocytes, leukocytes, neutrophils, and monocytes, and, it diminish lymphocytes, eosinophils, and the eosinophil/monocyte ratio ( 18 – 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the existing literature, certain BoF indices have been analyzed in patients with myocardial infarction, COVID-19 infection, or heart failure [ 28 , 29 , 30 ]; however, we could not find any data about BoF indices in a kidney transplant recipient population. Therefore, the aim of this study was to calculate some of the BoF indices in kidney transplant recipients, enabling the analysis of the relationship between the BoF indices and biopsy-proven transplant rejection.…”
Section: Introductionmentioning
confidence: 97%